STUDENT’S SELF REGULATION AGED 11-12 YEARS OLD IN SCHOOL THAT IMPLEMENTED FITRAH BASED EDUCATION - Anissaniwaty, Myrna; Pertiwi, Nisa Indah; Widyastuti, Linda; Isnandari, Aulia Fitriani; Kartika, Aqllah Indah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2023)
Accompanying the learning process of students is still a long mandate for parents and educators. Changes in the educational process that occurred as a result of the Covid-19 pandemic raised the need for students to improve their self-regulation ability in order to design more effective learning strategies, especially in terms of learning objectives. This study aims to obtain an overview of students' self-regulation in understanding learning objectives, carrying out their own learning plans and strategies, and monitoring independently how effective the learning process is. This research was conducted on four students who implemented fitrah based education. This research used descriptive qualitative method. Methods of data collection used observation and interviews. The results of this research showed that the cycle of self-regulation in students in schools that implemented fitrah based education has not been fully implemented. The forethought phase which is the beginning of the self-regulation cycle has not been carried out, so the subsequent phases are not running effectively.